Iron-based sulfate composite material as well as preparation method and application thereof
By surface acid treatment and aluminum doping of sodium ion battery positive electrode material sodium ferrous sulfate, and thermal shock reaction, the problems of low electronic conductivity and insufficient cycling performance are solved, and the material's plurality and cycling performance are significantly improved.
Patent Information
- Application Number
- CN202510242494.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-06-27
AI Technical Summary
The existing sodium ion battery cathode material sodium ferrous sulfate has a low electronic conductivity, resulting in low activity, and the carbon coating effect synthesized at low temperatures is not ideal, and the rate performance and cycling performance need to be further improved.
By surface acid treatment of carbon nanotubes and mixing them with FeSO4, Na2SO4 and Al2(SO4)3 for solid phase reaction, a carbon nanotube modified aluminum-doped sodium ferrous sulfate was obtained, followed by thermal shock reaction to improve the physical contact and electronic conductivity of the nanotubes and sodium ferrous sulfate.
The rate performance and cycling performance of the material are significantly improved, making it suitable as a high-performance positive electrode material for sodium ion batteries.
Smart Images

Figure CN120208298A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of the synthesis of cathode materials for sodium-ion batteries. More specifically, the present invention relates to an iron-based sulfate composite material, a preparation method thereof, and an application thereof. Background Art
[0002] Under the background of "carbon peak and carbon neutrality", using clean energy such as solar power generation and combining it with battery energy storage will replace the fossil energy power generation mode. Considering factors such as comprehensive price and technological maturity, lithium-ion batteries, especially lithium iron phosphate batteries, are currently the mainstream energy storage batteries. However, in the long run, lithium-ion batteries still face certain challenges in terms of safety, resources, and sustainability. In contrast, sodium-ion batteries, due to their high safety and resource sustainability, are suitable for large-scale energy storage. The cathode material is a key part of sodium-ion batteries. When choosing a suitable cathode, factors such as its cost, energy density, lifespan, and safety need to be comprehensively considered.
[0003] Common cathodes include Prussian blue-based materials, layered oxides, and polyanion materials. Among them, polyanion materials have no risk of oxygen evolution during charge and discharge and have good safety. Among polyanion materials, sodium iron sulfate has attracted much attention in recent years due to its low raw material cost, low preparation temperature, high working voltage, etc. However, the electronic conductivity of this material is relatively low, resulting in low activity, and its capacity can only be fully exerted at a relatively high voltage, and interfacial reactions between the electrolyte and the electrode material are likely to occur at high voltages. In addition, due to its synthesis at low temperatures, the in-situ carbon coating effect is not ideal, and it generally needs to be directly mixed with a conductive agent, but this will lead to uneven mixing and poor physical contact.
[0004] The prior art discloses a preparation method of a sodium iron sulfate cathode material for a sodium-ion battery and a vehicle. Anhydrous ferrous sulfate, sodium sulfate, a carbon source, and an aluminum source are heated and annealed in an inert gas to obtain the sodium iron sulfate cathode material. However, the carbon source has a poor wrapping effect on sodium iron sulfate, and the rate performance and cycle performance of the material still need to be further improved.
[0005] Therefore, it is of great research significance and application value to develop an iron-based sulfate composite material for sodium-ion battery cathodes, a preparation method thereof, and an application thereof, which have excellent rate performance and cycle performance. Summary of the Invention
[0006] The present invention aims to overcome the deficiencies of the prior art and provides an iron-based sulfate composite material, a preparation method thereof, and an application thereof, which are used as a cathode material for sodium-ion batteries and have excellent rate performance and cycle performance.
[0007] Therefore, the primary object of the present invention is to provide a preparation method of an iron-based sulfate composite material.
[0008] Another object of the present invention is to provide an iron-based sulfate composite material prepared by the above preparation method.
[0009] Another object of the present invention is to provide an application of the above iron-based sulfate composite material.
[0010] To achieve the above object, the present invention adopts the following technical solutions:
[0011] The present invention protects a preparation method of an iron-based sulfate composite material, comprising the following steps:
[0012] S1. Surface acid treatment of carbon nanotubes;
[0013] S2. Mix the carbon nanotubes treated in S1 with FeSO4, Na2SO4 and Al2(SO4)3, and carry out a solid-phase reaction under an inert atmosphere to obtain sodium aluminum-doped ferrous sulfate modified by carbon nanotubes, Na 2+2x Fe 2-x-1.5y Al y (SO4)3;
[0014] S3. Subject the sodium aluminum-doped ferrous sulfate obtained in S2 to a thermal shock reaction to obtain an iron-based sulfate composite material;
[0015] Wherein, 0≤x≤0.5, 0<y≤0.05;
[0016] The carbon nanotubes are multi-walled carbon nanotubes;
[0017] The number of thermal shock times of the thermal shock reaction is 10 to 30 times, and the thermal shock temperature of the thermal shock reaction is 300 to 400 °C;
[0018] The total weight ratio of the acid-treated carbon nanotubes to FeSO4, Na2SO4 and Al2(SO4)3 is (2 to 10):100.
[0019] After surface acid treatment, surface functional groups such as carboxyl groups and hydroxyl groups can be formed on the surface of carbon nanotubes. Compared with untreated carbon nanotubes, the uniformity of the mixture of carbon nanotubes and sodium ferrous sulfate precursor is improved, thereby improving the rate performance and cycle performance of the composite material. Through hetero-valent aluminum doping and carbon nanotube winding, the electronic conductivity of the material can be improved, thereby increasing the material capacity and rate performance. Aluminum doping can also improve the ionic conductivity and structural stability, thereby improving the rate performance and cycle performance, while carbon nanotube winding can also improve the interfacial stability with the electrolyte and cycle performance. Experiments have found that if homo-valent ion doping, such as magnesium ion doping, is used, the above effects cannot be achieved. The carbon nanotubes selected are oligomeric wall carbon nanotubes, and the number of carbon layers is usually 2-5 layers. Experiments have found that compared with single-wall carbon nanotubes, multi-wall carbon nanotubes or other carbon materials, oligomeric wall carbon nanotubes have better comprehensive properties such as electrical conductivity, mechanical properties, dispersion properties, and welding properties with sodium ferrous sulfate.
[0020] The thermal shock reaction is to rapidly heat the material to a certain temperature at a certain heating rate, then stay at this temperature for a certain period of time, and then rapidly cool down. The temperature is called the thermal shock temperature, and the time is called the thermal shock time. Experiments have found that through thermal shock at appropriate shock times and temperatures, welding may occur between carbon nanotubes and sodium ferrous sulfate, forming solder joints, thereby improving the physical contact between carbon nanotubes and sodium ferrous sulfate, improving the electronic conductivity, and thus increasing the capacity and rate performance. Thermal shock can also improve the winding effect of carbon nanotubes on sodium ferrous sulfate, reducing its contact with the electrolyte, thereby improving the cycle life. Thermal shock can also repair the acid-corroded carbon nanotubes and remove the surface functional groups on the carbon nanotubes.
[0021] Specifically, the thermal shock reaction uses a thermal shock device to carry out the thermal shock reaction. Joule heating is based on the effect that heat is generated due to resistance when an electric current passes through a conductive material. Heating is achieved within milliseconds through a high-current pulse, and the heating rate and peak temperature are controlled by adjusting the DC voltage and current. After heating, rapid cooling is carried out.
[0022] Preferably, in the chemical formula of the aluminum-doped sodium ferrous sulfate, 0.1 ≤ x ≤ 0.4 and 0.01 ≤ y ≤ 0.03. Experiments have found that within this range, an optimized balance of material capacity, rate performance, and cycle life can be achieved.
[0023] Preferably, the acid treatment in step S1 includes the following steps:
[0024] Add the carbon nanotubes to the acid solution, mix, then filter with deionized water and dry to obtain acid-treated carbon nanotubes.
[0025] Preferably, the acid is selected from nitric acid.
[0026] Preferably, the concentration of the acid solution is 5 - 10 mol / L.
[0027] Preferably, the temperature of the acid treatment is 100 - 180 °C.
[0028] Preferably, the time of the acid treatment is 2 - 10 h.
[0029] Preferably, the acid treatment further includes the steps of washing and drying.
[0030] Preferably, the mixing in step S2 is ball milling mixing.
[0031] Preferably, the inert atmosphere is one or more of nitrogen, argon or helium.
[0032] Preferably, the temperature of the solid-phase reaction in step S2 is 350 - 400 °C.
[0033] Preferably, the time of the solid-phase reaction in step S2 is 5 - 24 h.
[0034] Preferably, the heating rate of the thermal shock reaction in step S3 is 400 - 700 °C / s.
[0035] Preferably, the thermal shock temperature of the thermal shock reaction in step S3 is 300 - 400 °C.
[0036] Preferably, the thermal shock time of the thermal shock reaction in step S3 is 50 - 100 ms.
[0037] The present invention protects an iron-based sulfate composite material prepared by the above preparation method.
[0038] The application of the above iron-based sulfate composite material in the cathode material of a sodium-ion battery is also within the protection scope of the present invention.
[0039] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0040] The present invention provides an iron-based sulfate composite material. By acid-treating the surface of carbon nanotubes and then forming sodium aluminum-doped ferrous sulfate modified by carbon nanotubes, the thermal shock reaction enables the carbon nanotubes and sodium ferrous sulfate to be effectively welded to form solder joints, thereby improving the physical contact between the carbon nanotubes and sodium ferrous sulfate, improving the electronic conductivity. The material has excellent rate performance and cycle performance and can be used as the cathode material of a sodium-ion battery. Description of the Drawings
[0041] Figure 1 Schematic diagram of the iron-based sulfate composite material prepared in Example 1, 1. Sodium ferrous sulfate, 2. Carbon nanotubes, 3. Solder joints;
[0042] Figure 2Charge-discharge curve of a sodium-ion battery assembled with the iron-based sulfate composite material prepared in Example 1 as the positive electrode material;
[0043] Figure 3 Cycle life diagram of a sodium-ion battery assembled with the iron-based sulfate composite material prepared in Example 1 as the positive electrode material;
[0044] Figure 4 Charge-discharge curve of a sodium-ion battery assembled with the material prepared in Comparative Example 1 as the positive electrode material;
[0045] Figure 5 Cycle life diagram of a sodium-ion battery assembled with the material prepared in Comparative Example 1 as the positive electrode material. Detailed implementation manners
[0046] In order to more clearly and completely describe the technical solution of the present invention, the present invention will be further described in detail below through specific examples. It should be understood that the specific examples described herein are only used to explain the present invention and are not used to limit the present invention. Various changes can be made within the scope defined by the claims of the present invention.
[0047] Unless otherwise specified, the reagents and materials used in the following examples are all commercially available.
[0048] Test indicators:
[0049] Using the composite materials prepared in this example and the comparative example as the positive electrode active materials to assemble batteries for performance testing. The weight ratio of the positive electrode active material, conductive agent (Super P), and binder (PVDF) is 7:2:1. Assemble button batteries in a glove box, use metallic sodium as the negative electrode, glass fiber as the separator, and a 1mol / L NaPF6 propylene carbonate (PC) / ethyl methyl carbonate (EMC) solution as the electrolyte, and add 4% by weight of fluoroethylene carbonate (FEC) based on the weight of the above electrolyte. Perform constant current charge-discharge testing at room temperature, with the test voltage range of 2 - 4.3V and the current 1C set to 100mA / g.
[0050] (1) Discharge capacity (mAh / g): Charge the battery to 4.3V at a current density of 0.1C, and then discharge it to 2V at a current density of 0.1C. The capacity obtained at this time is recorded as the discharge capacity;
[0051] (2) Rate performance test: Charge the battery to 4.3V at a current density of 0.1C, and then discharge it to 2V at a current density of 0.1C. The discharge capacity obtained at this time is recorded as capacity Q1. Then charge the battery to 4.3V at a current density of 0.1C, and then discharge it to 2V at a current density of 10C. The discharge capacity obtained at this time is recorded as capacity Q2. Rate performance = Q2 / Q1 × 100%;
[0052] (3) Cycling test: Charge the battery at a current density of 1C to 4.3V, then discharge it at a current density of 1C to 2V. The discharge capacity obtained at this time is denoted as capacity Q1. Repeat the above test 299 more times, and the obtained discharge capacity is denoted as capacity Q2. Cycling performance = Q2 / Q1 × 100%.
[0053] Example 1 A ferrous sulfate composite material, its preparation method and application
[0054] The few-walled carbon nanotubes are acid-treated with a nitric acid concentration of 6 mol / L, an acid treatment time of 5 hours, and an acid treatment temperature of 150 °C. Then, using the acid-treated carbon nanotubes, FeSO4, Na2SO4, and Al2(SO4)3 as precursors, they are ball-milled and mixed, where the ball-milling time is 10 h, the ball-milling speed is 400 rpm, the molar ratio of FeSO4, Na2SO4, and Al2(SO4)3 is 1.685:1.3:0.005, and the total weight ratio of the acid-treated carbon nanotubes to FeSO4, Na2SO4, and Al2(SO4)3 is 4:100. Then, the ball-milled product is calcined in an argon atmosphere at 380 °C for 12 h to obtain Na 2.6 Fe 1.685 Al 0.01 (SO4)3 modified by few-walled carbon nanotubes. Finally, the above product is thermally shocked at 340 °C for 70 milliseconds, and the number of thermal shock times is 20 times to obtain the ferrous sulfate composite material.
[0055] Example 2 A ferrous sulfate composite material, its preparation method and application
[0056] The few-walled carbon nanotubes are acid-treated with a nitric acid concentration of 6 mol / L, an acid treatment time of 5 hours, and an acid treatment temperature of 150 °C. Then, using the acid-treated carbon nanotubes, FeSO4, Na2SO4, and Al2(SO4)3 as precursors, they are ball-milled and mixed, where the ball-milling time is 10 h, the ball-milling speed is 400 rpm, the molar ratio of FeSO4, Na2SO4, and Al2(SO4)3 is 1.77:1.2:0.01, and the total weight ratio of the acid-treated carbon nanotubes to FeSO4, Na2SO4, and Al2(SO4)3 is 7:100. Then, the ball-milled product is calcined in an argon atmosphere at 380 °C for 12 h to obtain Na 2.4 Fe 1.77 Al 0.02 (SO4)3 modified by few-walled carbon nanotubes. Finally, the above product is thermally shocked at 320 °C for 80 milliseconds, and the number of thermal shock times is 20 times to obtain the ferrous sulfate composite material, and its structural schematic diagram is shown in Figure 1 .
[0057] Example 3 A ferrous sulfate composite material, its preparation method and application
[0058] The few-walled carbon nanotubes are subjected to acid treatment with a nitric acid concentration of 6 mol / L, an acid treatment time of 5 hours, and an acid treatment temperature of 150 °C. Then, the acid-treated carbon nanotubes, FeSO4, Na2SO4, and Al2(SO4)3 are used as precursors and mixed by ball milling. The ball milling time is 10 h, the ball milling speed is 400 rpm, the molar ratio of FeSO4, Na2SO4, and Al2(SO4)3 is 1.585:1.4:0.005, and the total weight ratio of the acid-treated carbon nanotubes to FeSO4, Na2SO4, and Al2(SO4)3 is 5:100. The ball-milled product is then calcined in an argon atmosphere at 380 °C for 12 h to obtain Na 2.8 Fe 1.585 Al 0.01 (SO4)3 modified by few-walled carbon nanotubes. Finally, the above product is thermally shocked at 360 °C for 60 milliseconds with 20 thermal shock times to obtain an iron-based sulfate composite material.
[0059] Example 4 An iron-based sulfate composite material, its preparation method and application
[0060] The few-walled carbon nanotubes are subjected to acid treatment with a nitric acid concentration of 6 mol / L, an acid treatment time of 5 hours, and an acid treatment temperature of 150 °C. Then, the acid-treated carbon nanotubes, FeSO4, Na2SO4, and Al2(SO4)3 are used as precursors and mixed by ball milling. The ball milling time is 10 h, the ball milling speed is 400 rpm, the molar ratio of FeSO4, Na2SO4, and Al2(SO4)3 is 1.855:1.1:0.015, and the total weight ratio of the acid-treated carbon nanotubes to FeSO4, Na2SO4, and Al2(SO4)3 is 5:100. The ball-milled product is then calcined in an argon atmosphere at 380 °C for 12 h to obtain Na 2.2 Fe 1.855 Al 0.03 (SO4)3 modified by few-walled carbon nanotubes. Finally, the above product is thermally shocked at 380 °C for 50 milliseconds with 20 pulse times to obtain an iron-based sulfate composite material.
[0061] Example 5 An iron-based sulfate composite material, its preparation method and application
[0062] The experimental method is the same as that in Example 1, except that the number of thermal shock times is 10 times.
[0063] Example 6 An iron-based sulfate composite material, its preparation method and application
[0064] The experimental method is the same as that in Example 1, except that the number of thermal shock times is 30 times.
[0065] Example 7 An iron-based sulfate composite material, its preparation method and application
[0066] The experimental method was the same as that in Example 1, except that the temperature of thermal shock was 300 °C.
[0067] Example 8 An iron-based sulfate composite material, its preparation method and application
[0068] The experimental method was the same as that in Example 1, except that the molecular formula of the iron-based sulfate was Na 2.2 Fe 1.885 Al 0.01 (SO4)3.
[0069] Example 9 An iron-based sulfate composite material, its preparation method and application
[0070] The experimental method was the same as that in Example 1, except that the molecular formula of the iron-based sulfate was Na 2.8 Fe 1.555 Al 0.03 (SO4)3.
[0071] Comparative Example 1 An iron-based sulfate composite material, its preparation method and application
[0072] The experimental method was the same as that in Example 1, except that the step of thermal shock reaction was not carried out, and the obtained multi-walled carbon nanotube-modified Na 2.4 Fe 1.77 Al 0.02 (SO4)3 was directly used as the composite material.
[0073] Comparative Example 2 An iron-based sulfate composite material, its preparation method and application
[0074] The experimental method was the same as that in Example 1, except that the number of thermal shock times was 5 times.
[0075] Comparative Example 3 An iron-based sulfate composite material, its preparation method and application
[0076] The experimental method was the same as that in Example 1, except that the number of thermal shock times was 50 times.
[0077] Comparative Example 4 An iron-based sulfate composite material, its preparation method and application
[0078] The experimental method was the same as that in Example 1, except that the temperature of thermal shock was 250 °C.
[0079] Comparative Example 5 An iron-based sulfate composite material, its preparation method and application
[0080] The experimental method was the same as that in Example 1, except that the temperature of thermal shock was 500 °C.
[0081] Comparative Example 6 An iron-based sulfate composite material, its preparation method and application
[0082] The experimental method was the same as that of Example 1, except that the carbon nanotubes were not subjected to surface acid treatment.
[0083] Comparative Example 7 An iron-based sulfate composite material, its preparation method and application
[0084] The experimental method was the same as that of Example 1, except that the carbon nanotubes were multi-walled carbon nanotubes.
[0085] Comparative Example 8 An iron-based sulfate composite material, its preparation method and application
[0086] The experimental method was the same as that of Example 1, except that the carbon nanotubes were single-walled carbon nanotubes.
[0087] Comparative Example 9 An iron-based sulfate composite material, its preparation method and application
[0088] The experimental method was the same as that of Example 1, except that the weight ratio of the acid-treated carbon nanotubes to the total weight of FeSO4, Na2SO4 and Al2(SO4)3 was 1:100.
[0089] Comparative Example 10 An iron-based sulfate composite material, its preparation method and application
[0090] The experimental method was the same as that of Example 1, except that the weight ratio of the acid-treated carbon nanotubes to the total weight of FeSO4, Na2SO4 and Al2(SO4)3 was 15:100.
[0091] Comparative Example 11 An iron-based sulfate composite material, its preparation method and application
[0092] The experimental method was the same as that of Example 1, except that acetylene black was used instead of oligomeric carbon nanotubes.
[0093] Comparative Example 12 An iron-based sulfate composite material, its preparation method and application
[0094] The experimental method was the same as that of Example 1, except that aluminum was not doped, and the chemical formula of sodium ferrous sulfate was Na 2.4 Fe 1.8 (SO4)3.
[0095] Comparative Example 13 An iron-based sulfate composite material, its preparation method and application
[0096] The experimental method was the same as that of Example 1, except that Al2(SO4)3 was replaced with an equal amount of magnesium as the doping element, and MgSO4 was used instead of Al2(SO4)3 during material synthesis. The chemical formula of sodium ferrous sulfate was Na 2.4 Fe 1.78 Mg 0.02 (SO4)3.
[0097] Comparative Example 14 An iron-based sulfate composite material, its preparation method and application
[0098] The experimental method was the same as that of Example 1, except that the nitric acid solution was changed to a NaOH solution with the same concentration.
[0099] Table 1 Experimental test results of Examples and Comparative Examples
[0100]
[0101]
[0102] According to Table 1, the iron-based sulfate composites prepared in Examples 1-9 were used as the cathode material of sodium-ion batteries, with excellent rate performance and cycling performance, and the performance of Example 1 was the best.
[0103] There was no thermal shock in Comparative Example 1, the number of thermal shocks in Comparative Example 2 was too small, and the thermal shock temperature in Comparative Example 4 was too low, so that the full welding of carbon nanotubes and sodium ferrous sulfate could not be achieved; the number of thermal shocks in Comparative Example 3 was too large, and the thermal shock temperature in Comparative Example 5 was too high, which would cause the decomposition of sodium ferrous sulfate; the carbon nanotubes used in Comparative Example 6 were not surface acid-treated, the uniformity of the mixture of carbon nanotubes and sodium ferrous sulfate precursor was low, and the rate performance and cycling performance of the composite material were poor; the carbon nanotubes used in Comparative Example 7 were multi-walled carbon nanotubes, and the carbon nanotubes used in Comparative Example 8 were single-walled carbon nanotubes, both of which did not have the excellent comprehensive performance of few-walled carbon nanotubes; the amount of carbon nanotubes added in Comparative Example 9 was small, the conductivity of the composite material was low, and the winding effect of carbon nanotubes was not good, which was not conducive to the improvement of the rate performance and cycling life of the product; the amount of carbon nanotubes added in Comparative Example 10 was too large, the conductivity was good, and the rate performance was improved to a certain extent. When the amount of carbon nanotubes added was higher than this value, the capacity of the composite material decreased, and the uneven distribution of carbon nanotubes would also be caused; acetylene black was used instead of carbon nanotubes in Comparative Example 11; aluminum was not doped in Comparative Example 12, and the rate performance and cycling performance of the material were poor; magnesium was used instead of aluminum in Comparative Example 13, and the improvement of rate performance and cycling performance could not be achieved; the carbon nanotubes were treated with alkali in Comparative Example 14, and the effect was poor.
[0104] Obviously, the above-mentioned embodiments of the present invention are merely examples for clearly illustrating the present invention, rather than limiting the implementation manners of the present invention. For those of ordinary skill in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to enumerate all implementation manners here. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing an iron-based sulfate composite material, characterized in that: The following steps are involved: S1. treating the surface of carbon nanotubes with acid; S2. The carbon nanotubes treated in S1. are mixed with FeSO4, Na2SO4 and Al2(SO4)3, and solid phase reaction is performed under an inert atmosphere to obtain aluminum-doped sodium ferrous sulfate modified with carbon nanotubes. 2+2x Fe 2-x-1.5y Al y (SO4)3; S3. thermal shock reaction of the aluminum-doped sodium ferrous sulfate obtained in S2. to obtain an iron-based sulfate composite material; Wherein, 0≤x≤0.5, 0<y≤0.05; The carbon nanotubes are oligo-walled carbon nanotubes; The thermal shock times of the thermal shock reaction are 10 to 30 times, and the thermal shock temperature of the thermal shock reaction is 300 to 400° C.; The total weight ratio of acid-treated carbon nanotubes to FeSO4, Na2SO4 and Al2(SO4)3 is (2-10):
100.
2. The method according to claim 1, characterized in that In the chemical formula of the aluminum-doped sodium ferrous sulfate, 0.1≤x≤0.4, 0.01≤y≤0.
03.
3. The method according to claim 1, characterized in that The acid treatment method comprises the following steps: adding the carbon nanotubes into an acid solution, soaking the mixture, filtering the mixture with deionized water, and drying the mixture to obtain the carbon nanotubes treated with the acid.
4. The method according to claim 1, characterized in that: The concentration of the acid solution is 5-10 mol / L.
5. The method according to claim 1, characterized in that The temperature of the solid phase reaction in step S2 is 350-400°C.
6. The method according to claim 1, characterized in that The solid phase reaction time in step S2 is 5 to 24 hours.
7. The method according to claim 1, characterized in that The heating rate of the thermal shock reaction in step S3 is 400-700° C. / s.
8. The method according to claim 1, characterized in that The thermal shock time of the thermal shock reaction in step S3 is 50 to 100 ms.
9. An iron-based sulfate composite material, characterized in that It is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the iron-based sulfate composite material according to claim 9 in a positive electrode material for a sodium ion battery.
Citation Information
Cited By
Preparation method of high-rate-performance sodium ferric sulfate positive electrode material, positive electrode material, electrode plate and sodium ion battery
CN122158670A